Znanje, stavovi i samoevaluacija medicinskih sestara u vezi sa kliničkim istraživanjima - Stoisavljević Šatara, Svjetlana; Stojaković, Nataša; Golić Jelić, Ana; Maksimović, Žana M; Gajić Bojić, Milica; Petrović Tepić, Snežana (Scripta Medica, 2023)
Background/Aim. Clinical research nurse is a well-known concept in Europe and other countries. The purpose of this study was to investigate the nurses’ knowledge and attitudes towards clinical research and their opinions and self-evaluation about clinical research nursing, and factors affecting them. Methods. A cross sectional study was conducted at the University Clinical Centre of the Republic of Srpska (UCCRS). A questionnaire included 50 questions/statements was created in order to address the aims of the research and afterwards distributed to 120 nurses from 6 departments. Results. Response rate was 91.6 %. Most of the respondents showed a low level of knowledge, but positive attitude related to clinical research. Nurses who participated in clinical research were confident in their competencies according to their self-evaluation. Conclusion. Systematic approach to the additional nurses education could have a significant impact on a success of clinical research.